Use of pasteurised human donor milk across neonatal networks in England - Battersby,C; Mousinho,RMA; Longford,N; Modi,N (EARLY HUMAN DEVELOPMENT, 2018)
ObjectivesTo describe the use of pasteurised human donor milk (pHDM) in England and the influence of a human milk bank in the network.DesignProspective observational studySettingAll 163 neonatal units (23 networks) in England 2012–2013.PatientsPreterm infants born at <32weeks gestational age (GA).Main outcome measuresProportion of infants and care-days fed pHDM during the first 30 postnatal days by networkMethodsWe extracted daily patient-level data from the National Neonatal Research Database (NNRD). We fitted a logistic regression of pHDM exposure on the presence of a pHDM bank within the network, with GA, BW z score and network as covariates. Significance was assessed by the likelihood ratio (chi-squared) test.ResultsData for 13,463 infants were included in the study. Across the networks, the proportion (95%CI) of infants ranged from 2.0% (1.0, 3.0) to 61.0% (57.4%, 64.6%), and the proportion of care-days in which pHDM was fed from 0.08% (0.04%, 0.10%) to 21.9% (19.9%, 24.0%). In three networks <5%, and in seven networks >30% of infants received any pHDM. Variation in the use of pHDM across networks remained significant after adjustment for presence of a human milk bank within the network and all covariates (p<0.001).ConclusionsWide variation of pHDM use in England is not fully explained by presence of a pHDM bank or patient characteristics. This suggests clinical uncertainty about the use of pHDM.